Characterisation and performance evaluation of developed alternative polymer abrasive gels for abrasive flow finishing process. (2015) - Sambharia, JaiKishan; Mali, Harlal Singh
In abrasive flow finishing (AFF), media is the key element that dominates the finishing behaviour. However, commercially available abrasive media are very expensive and its affordability is an issue, especially for price sensitive industries. Lower cost alternative AFM media are developed which consists of base polymers, additives and liquid synthesiser by uniformly mixing them to become the flexible polymer abrasive gels. Effects of abrasive concentrations, temperature, abrasive mesh size and percentage of liquid synthesiser on viscosity of polymer abrasive gel have been studied to characterise the rheology of developed gels. Developed alternative polymer abrasive gel can withstand up to 100°C. It is found that the average surface roughness (Ra ) decreased from 3.5 µm to 0.60 µm after 50 machining cycles and 60 weight percentage abrasive concentrations. In similar conditions 0.6-1.3 mg of material got removed from HSS trim dies based on different viscosity grades of developed polymer abrasive gels.